THE ISSUE OF MUNICIPAL TRANSPORT PREFERENCE - Kupculjakova, Jana (Doprava a spoje, 2011)
One of the main criteria in choosing the means of transport is the transfer time. It is the time required for walking to the bus stop, waiting time for bus connection, and time spent in the vehicle, and time required for eventual transfer, and finally time to walk from the bus stop. It follows that if the transfer time is shorter municipal transport becomes more attractive for passengers. The paper deals with the issue of municipal transport preference. It describes the basic way of the municipal transport preference.